Temporal variation in environmental DNA detections within an urban estuary - Joseph D. DiBattista; Ashley M. Fowler; David Harasti; Robert Hitchen; Nicole McMahon; Shaun P. Wilkinson (Regional Studies in Marine Science, 2026)

Does the 2-test in vitro genotoxicity battery of Ames plus in vitro micronucleus tests detect relevant substances that induce gene mutations in vivo? - David Kirkland; Damian Bowen; Paul Fowler (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Continent-wide stock structure and connectivity of silver trevally (Pseudocaranx georgianus) based on population genomics and otolith shape and chemistry - Zoriana H.T. Lam; John Stewart; Jonathan Sandoval-Castillo; Patrick Reis-Santos; Rhiannon A. Van Eck; Bronwyn M. Gillanders; Peter Ritchie; Maren Wellenreuther; Charlie Huveneers; David V. Fairclough; Ashley M. Fowler; Julian Hughes; et al. (Fisheries Research, 2026)

Mechanisms of Strong Hearts, Healthy Communities-2.0 Effects on Weight: A Mediation Analysis - Chad D. Rethorst; Margaret Demment; Meredith L. Graham; Seungyeon Ha; Alexandra L. MacMillan Uribe; Brian K. Lo; Jacob Szeszulski; Phrashiah Githinji; David Strogatz; Sara C. Folta; Miriam E. Nelson; Rebecca A. Seguin-Fowler (Journal of Nutrition Education and Behavior, 2026)

Low foliar nitrogen and elevated defensive metabolites in the invasive weed Calluna vulgaris (heather) may impair biocontrol agent performance - D. Paul Barrett; Maria A. Minor; Paul Peterson; Simon V. Fowler; Arvind K. Subbaraj; David J. Lun; Andrea Clavijo McCormick (Biological Invasions, 2026)
Introducing insect biocontrol agents to manage invasive plants is an effective and sustainable management option. However, biocontrol agents sometimes fail to establish or are ineffective in the new range. Heather beetle Lochmaea suturalis, (Thomson, 1866) (Coleoptera: Chrysomelidae) sourced from the United Kingdom (UK), was introduced into New Zealand’s North Island Central Plateau (CP) to control invasive Calluna vulgaris (L.) Hull (heather). The beetle was difficult to establish and the few populations that did, achieved poor population growth rates and expansion in contrast to the rapid rates associated with its conspecifics in the UK. We hypothesize that low soil nutrients such as nitrogen and phosphorous (N and P) on the CP may be linked to changes in C. vulgaris’ primary nutritional and secondary defensive metabolites, leading to poor beetle performance. Testing this hypothesis involved application of N and P to soil in C. vulgaris field plots, measurement of foliar N and Carbon (C), plus using non-targeted metabolomics, exploring differences in the primary and secondary metabolites between treatments. Raising soil nutrients amplified several primary metabolites including N-based amino acids and concomitantly reduced the majority of phenylpropanoids, a secondary metabolite group containing many defensive compounds. This work seeks to better understand, how abiotic conditions in a new environment, influence invasive plant metabolism, potentially altering the efficiency of foliage assimilation which may impair biocontrol agent establishment and effectiveness. Such understanding may be applied to mitigate potential foliar deficiencies at release sites and contribute to improving success rates of biocontrol as a management strategy for invasive plants.

Raman spectroscopy is a non-invasive method to predict the total viable microbial count through the packaging material of vacuum packaged lamb meat - Benjamin W.B. Holman; David L. Hopkins; Stephanie M. Fowler (Meat Science, 2025)

Marine data assimilation in the UK: the past, the present, and the vision for the future - Jozef Skákala; David Ford; Keith Haines; Amos Lawless; Matthew J. Martin; Philip Browne; Marcin Chrust; Stefano Ciavatta; Alison Fowler; Daniel Lea; Matthew Palmer; Andrea Rochner; et al. (Ocean Science, 2025)
In the last 2 decades, UK research institutes have led a wide range of developments in marine data assimilation (MDA), covering areas from operational applications in physics and biogeochemistry to fundamental theory. We highlight the emergence of strong collaboration in the UK MDA community over this period and the increasing unification of its tools. We focus on identifying the MDA stakeholder community and current/future areas of impact, as well as current trends and future opportunities. This includes the rapid growth of machine learning (ML)/artificial intelligence (AI) and digital-twin applications. We articulate a vision for the future, including the need for future types of observational data (whether planned missions or hypothetical) and how the community should respond to increases in computational power and new computer architectures (e.g. exascale computing). We contrast the requirements of different MDA areas, including physics, biogeochemistry, and coupled data assimilation (DA). Although the specifics of the vision depend on each area, common themes emerge. We advocate for balanced redistribution of new computational capability among increased model resolution, model complexity, more sophisticated DA algorithms, and uncertainty representation (e.g. ensembles). We also advocate for integrated approaches, such as strongly coupled DA (ocean–atmosphere, physics–biogeochemistry, and ocean–sea ice) and the use of ML/AI components (e.g. for multivariate increment balancing, bias correction, model emulation, observation re-gridding, or fusion).

Decision-making and ecosystem service dimensions of managed dyke realignment in the complex coastal landscapes of the Bay of Fundy - Lara Cornejo; Elson Ian Nyl Ebreo Galang; Kate Sherren; Jeremy Lundholm; Danika van Proosdij; Will Balser; Elena Bennett; Tony M. Bowron; Kirsten Ellis; Jonathan Fowler; Jennifer Graham; Patrick James; et al. (Ocean & Coastal Management, 2025)

Patterns and drivers of movement in the estuary-associated sparid Acanthopagrus australis from a large-scale tagging study - Holly Gunton; Ashley M. Fowler; David J. Booth; John Stewart (Fisheries Research, 2025)

Panta Rhei: a decade of progress in research on change in hydrology and society - Heidi Kreibich; Murugesu Sivapalan; Amir AghaKouchak; Nans Addor; Hafzullah Aksoy; Berit Arheimer; Karsten Arnbjerg-Nielsen; Cynthia Vail-Castro; Christophe Cudennec; Mariana Madruga de Brito; Giuliano Di Baldassarre; David C. Finger; et al. (Hydrological Sciences Journal, 2025)

Early life history traits and elevated growth trajectories associated with survival into winter in range-expanding coral reef fish - Alexander L. Rigg; Ashley M. Fowler; Brigitte Sommer; David J. Booth (Marine Biology, 2025)
Climate change is driving the poleward range expansion of sub-tropical and tropical marine species into temperate ecosystems, with ocean-warming hotspots experiencing rapid shifts in species distributions. While recruitment to temperate waters by expatriating tropical vagrant fish is increasing, surviving through the cooler winters remains a significant barrier to their establishment. This study investigates the links between early life history traits and survival into winter in the Sergeant Major ( Abudefduf vaigiensis ), a tropical damselfish expanding its range into temperate southeastern Australia. Using otolith microstructure analysis, we reconstructed the early life histories of 122 individuals collected from rocky reefs in Sydney (33.8 o S) Australia in 2022 and 2023 and assessed their early life history traits. Our results demonstrate that individuals sampled during winter (hereafter “wintered fish”) had a larger size at hatching, longer pelagic larval duration, and higher body condition than fish collected before winter. Lower settlement water temperatures were positively associated with winter survival, indicating that a settlement date closer to the onset of winter was favourable. Additionally, wintered fish, exhibited higher growth rates in early life compared to fish sampled prior to winter onset. These findings suggest that some early life history traits are selected for survival into winter, potentially mediating the physiological impacts of declining water temperature. If such traits increase overwinter survival they may facilitate the establishment of this range-expanding species in temperate rocky reef environments.

Faster larval growth and shorter pelagic duration enhance the post-settlement persistence of a common range-extending coral-reef fish in a temperate ecosystem - Alexander L. Rigg; Ashley M. Fowler; Ivan Nagelkerken; David J. Booth (Coral Reefs, 2025)
Climate-induced ocean warming facilitates the poleward range expansion of tropical marine species into temperate waters. Such tropicalisation is reshaping marine ecosystems globally and has ecological implications. Our understanding of the factors influencing the establishment and persistence of vagrant tropical species in temperate waters remains limited. To address this knowledge gap, we examined which early life history traits affect the post-settlement persistence of a vagrant tropical fish, the sergeant major damselfish Abudefduf vaigiensis , in temperate waters off southeast Australia. Over an 8-week period, fish were collected, and otolith microstructure analysis indicated that early post-settlement persistence was linked to fast larval growth in the week prior to settlement and to shorter pelagic larval duration, but not body size at hatching or body size at settlement. We conclude that successful invasions of temperate ecosystems by this vagrant tropical fish is likely mediated by demographic advantages these fish gain as early-stage larvae.

Overwintering performance of three juvenile temperate estuarine fishes - Clara Bellotto; Ashley M. Fowler; David J. Booth (Journal of Experimental Marine Biology and Ecology, 2025)

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Updated assessment of the genotoxic potential of titanium dioxide based on reviews of in vitro comet, mode of action and cellular uptake studies, and recent publications - David Kirkland; Arne Burzlaff; Andreas Czich; Shareen H. Doak; Paul Fowler; Stefan Pfuhler; Leon F. Stankowski (Regulatory Toxicology and Pharmacology, 2024)

Continued development of a tool to measure intramuscular fat of Australian lamb carcases in commercial situations - Stephanie M. Fowler; Stephen Morris; Suzanne I. Mortimer; David L. Hopkins (Meat Science, 2024)

Individual performance niches and responses to winter temperature change in three estuarine fishes from eastern Australia - Clara Bellotto; Ashley M. Fowler; David J. Booth (Marine Biology, 2024)
Climate change may impact individual organisms in different ways, a consideration often overshadowed by predominant focus on population effects in studies. We examined three estuarine fish species to determine if individual fish performance, persisted across winter water temperatures. Fish performance at 16 °C (current Sydney winter estuarine water temperature) and 20 °C (predicted under climate change) with low and high food regimes was assessed using key physiological (growth, aerobic scope, burst speed) and behavioural parameters (foraging activity, boldness, shelter usage, predator escape response). We expected a strong positive relationship between performance at 16 °C and 20 °C for each parameter, and interactions with food level, however in general this was not found for any species. Relative performance was only maintained across temperatures for a few parameters, such as bite rate, boldness, and shelter response in one species (trumpeter Pelates sexlineatu s), with aerobic scope in silver biddy Gerres subfasciatus , and boldness in fortescue Centropogon australis . Our results suggest that individuals’ fitness (directly via changes in growth, indirectly via behaviours) might be impacted by climate warming due to differences in relative performance among juvenile individuals across water temperatures. Changes in relative performance among individuals may initially compensate for a population-level response, thereby buffering the effects of climate change.

Validation of Raman spectroscopic models to verify the origin of Australian beef grown under different production systems - Stephanie M. Fowler; Matthew Kerr; David L. Hopkins; Leigh M. Schmidtke (Meat Science, 2024)

Self-swabbing versus assisted swabbing for viral detection by qRT-PCR: the experience from SARS-CoV-2 based on a meta-analysis of six prospectively designed evaluations conducted in a UK setting - Tom Fowler; David Chapman; Matthias E. Futschik; Sarah A. Tunkel; Edward Blandford; Elena Turek; Olumide Kolade; Sergio Souza da Cunha; Andrew Dodgson; Paul Klapper; Malur Sudhanva; Lindsey Davies; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Purpose In April 2020, the UK Government implemented NHS Test and Trace to provide SARS-CoV-2 quantitative reverse transcription polymerase chain reaction (qRT-PCR) testing for the public, with nose-and-throat swabbing for samples performed by trained staff. Self-swabbing (SS) would allow rapid scale-up of testing capacity and access. Six studies were undertaken to determine whether SS was as effective for detecting SARS-CoV-2 as swabbing performed by trained staff. Methods Six prospective studies were conducted between April–October 2020, using six swab/media combinations. Differences between assisted swabbing (AS) and SS were evaluated for concordance, positivity, sensitivity, cycle threshold (Ct) values and void rates. Statistical analysis was performed using 95% confidence intervals (CIs), paired t-tests and model-based methods. Results Overall, 3,253 individuals were recruited (median age 37 years, 49% female), with 2,933 having valid paired qRT-PCR results. Pooled concordance rate was 98% (95% CI: 96%, 99%). Positivity rate differences for SS (8.1%) and AS (8.4%) and differences in pooled sensitivities between SS (86%; 95% CI: 78%, 92%) and AS (91%; 95% CI: 78%, 96%) were nonsignificant. Both types of swabbing led to pooled void rates below 2% and strongly correlated Ct values. Age, sex and previous swabbing experience did not have a significant impact on concordance or sensitivity. Conclusion The UK adopted a policy to promote self-testing for SARS-CoV-2 based on data demonstrating equivalence of SS versus AS. Positive outcomes with SS are likely generalisable to testing for other respiratory pathogens, and we consider self-sampling and self-testing essential for future pandemic preparedness.

How uncertain and observable are marine ecosystem indicators in shelf seas? - Jozef Skákala; David Ford; Alison Fowler; Dan Lea; Matthew J. Martin; Stefano Ciavatta (Progress in Oceanography, 2024)

Utilization of an Advanced Sensor network to determine fuel heating value and Real-Time net unit heat rate during transient operation - Keane Stewart; Connor Moran; Kensley Fowler; David McFarland; Kody Powell; Jacob Tuttle; Andrew Fry (Fuel, 2024)

Mineral–water reactions in Earth’s mantle: Predictions from Born theory and ab initio molecular dynamics - Sarah J. Fowler; David M. Sherman; John P. Brodholt; Oliver T. Lord (Geochimica et Cosmochimica Acta, 2024)

Evaluating real-world emissions from in-use buses and taxis using on-road remote sensing - Mounisai Siddartha Middela; Srinath Mahesh; Aonghus McNabola; William Smith; David Timoney; Ali Ekhtiari; Ben Fowler; Paul Willis; Rebecca Rose; Jasmine Wareham; Hannah Walker; Bidisha Ghosh (Environmental Pollution, 2024)

Predator-avoidance behaviour of target and non-target temperate reef fishes is lower in areas protected from fishing - David A. Feary; Ashley M. Fowler; David J. Booth (Marine Biology, 2024)
The effects of hunting on predator-avoidance behaviour are increasingly being recognised on land but have received less attention in marine systems. We examined whether predator-avoidance behaviour of temperate reef fishes differed between areas protected and not protected from recreational fishing by examining the flight-initiation distance (FID; the distance a predator can approach before the prey animal flees) of six common species in southeastern Australia. By testing species that ranged in desirability to recreational fishers, we could determine if behavioural differences were specific to target species or extended more broadly throughout the assemblage. After accounting for potential variability among sites within protection levels, we found that the FID of all species was higher in fished areas than protected areas, with FID up to 2.4 times higher in fished areas. The two commonly targeted species had the greatest FID response to fishing. FID also increased with body size for all but one species. Our findings indicate the potential for assemblage-wide effects of fishing on predator-avoidance behaviour and are consistent with an indirect mechanism of behavioural modification.

Staining protocols affect use of otolith to estimate the demography of the damselfish sergeant major ( Abudefduf vaigiensis ) - Alexander L. Rigg; Clara Bellotto; Ashley M. Fowler; David J. Booth (Journal of Fish Biology, 2024)
This study assessed the otolith (sagittae, lapilli, and asterisci) increment deposition rate in the range‐shifting damselfish, A. vaigiensis , using different concentrations of Alizain Red S and evaluated the impact of staining on increment width. Daily increment deposition was verified in all otolith types and presented clearer fluorescent markings in the lapilli and sagittae than the asterisci, with high stain concentration showing the best clarity. Higher stain concentrations were found to decrease increment width, suggesting care is needed when using stained otoliths as a proxy for growth for this species.

Developing expert scientific consensus on the environmental and societal effects of marine artificial structures prior to decommissioning - Antony M. Knights; Anaëlle J. Lemasson; Louise B. Firth; Todd Bond; Jeremy Claisse; Joop W.P. Coolen; Andrea Copping; Jennifer Dannheim; Michela De Dominicis; Steven Degraer; Michael Elliott; Paul G. Fernandes; et al. (Journal of Environmental Management, 2024)

To what extent can decommissioning options for marine artificial structures move us toward environmental targets? - Antony M. Knights; Anaëlle J. Lemasson; Louise B. Firth; Nicola Beaumont; Silvana Birchenough; Jeremy Claisse; Joop W.P. Coolen; Andrea Copping; Michela De Dominicis; Steven Degraer; Michael Elliott; Paul G. Fernandes; et al. (Journal of Environmental Management, 2024)

Subtropical coral expansion into SE Australia: a haven for both temperate and expatriating tropical reef fishes - Max J. O’Connell; Ashley M. Fowler; Sam J. Allan; Giglia A. Beretta; David J. Booth (Coral Reefs, 2023)
We examined reef fish assemblages in and adjacent to a newly established coral bed (subtropical Pocillopora aliciae ) in temperate south-eastern Australia, to understand whether novel coral habitat is facilitating assemblages of range-expanding tropical and local temperate fishes. This is the first comprehensive assessment of fish species associating with this novel coral habitat within a temperate environment. Twenty fish species were observed associating with the coral (8 tropical and 12 temperate). Both temperate and tropical species were observed at greater (up to 48 times higher) densities on the coral than on nearby temperate rocky reef in the area, suggesting that the corals generally concentrate fish and may aid in tropicalisation for species that use subtropical coral as habitat. Future research should investigate the ongoing expansion of this coral, the relative quality of coral habitat for fish in temperate regions and the potential implications for functioning of temperate rocky reef ecosystems.

Toward sustainable harvest strategies for marine fisheries that include recreational fishing - Ashley M. Fowler; Natalie A. Dowling; Jeremy M. Lyle; Josep Alós; Leif E. Anderson; Steven J. Cooke; Andy J. Danylchuk; Keno Ferter; Heath Folpp; Clifford Hutt; Kieran Hyder; Daniel K. Lew; et al. (Fish and Fisheries, 2023)
Recreational fishing (RF) is a large yet undervalued component of fisheries globally. While progress has been made in monitoring, assessing, and managing the sector in isolation, integration of RF into the management of multi‐sector fisheries has been limited, particularly relative to the commercial sector. This marginalises recreational fishers and reduces the likelihood of achieving the sector's objectives and, more broadly, achieving fisheries sustainability. We examined the nature and extent of RF inclusion in harvest strategies (HSs) for marine fisheries across 15 regions in 11 nations to define the gap in inclusion that has developed between sectors. We focused on high‐income nations with a high level of RF governance and used a questionnaire to elicit expert knowledge on HSs due to the paucity of published documents. In total, 339 HSs were considered. We found that RF inclusion in HSs was more similar to the small‐scale sector (i.e., artisanal, cultural, or subsistence) than the commercial sector, with explicit operational objectives, data collection, performance indicators, reference points, and management controls lacking in many regions. Where specified, RF objectives focused on sustainability, economic value and catch allocation rather than directly relating to the recreational fishing experience. Conflicts with other sectors included competition with the commercial sector for limited resources, highlighting the importance of equitable resource allocation policies alongside HSs. We propose that RF be explicitly incorporated into HSs to ensure fisheries are ecologically, economically, and socially sustainable, and we recommend that fisheries organisations urgently review HSs for marine fisheries with a recreational component to close the harvest strategy gap among sectors.

Phylogenomics reveals extreme gene tree discordance in a lineage of dominant trees: hybridization, introgression, and incomplete lineage sorting blur deep evolutionary relationships despite clear species groupings in Eucalyptus subgenus Eudesmia - Todd G.B. McLay; Rachael M. Fowler; Patrick S. Fahey; Daniel J. Murphy; Frank Udovicic; David J. Cantrill; Michael J. Bayly (Molecular Phylogenetics and Evolution, 2023)

The utility of otolith-based methods for discriminating stock structure of the fishery important monacanthid, Nelusetta ayraud, over an intermediate scale - Holly Gunton; Ashley M. Fowler; Marcus E. Miller; David J. Booth; John Stewart (Fisheries Research, 2023)

Internal endpoint temperature (level of cooking doneness) effects on the fatty acid and mineral profiles of grilled lamb m. longissimus lumborum - Benjamin W.B. Holman; Stephanie M. Fowler; Kristy L. Bailes; Richard G. Meyer; David L. Hopkins; Edward H. Clayton (Meat Science, 2023)

Extensive regional variation in the phenology of insects and their response to temperature across N orth A merica - Peter O. Dunn; Insiyaa Ahmed; Elise Armstrong; Natasha Barlow; Malcolm A. Barnard; Marc Bélisle; Thomas J. Benson; Lisha L. Berzins; Chloe K. Boynton; T. Anders Brown; Melissa Cady; Kyle Cameron; et al. (Ecology, 2023)
Climate change models often assume similar responses to temperatures across the range of a species, but local adaptation or phenotypic plasticity can lead plants and animals to respond differently to temperature in different parts of their range. To date, there have been few tests of this assumption at the scale of continents, so it is unclear if this is a large‐scale problem. Here, we examined the assumption that insect taxa show similar responses to temperature at 96 sites in grassy habitats across North America. We sampled insects with Malaise traps during 2019–2021 ( N = 1041 samples) and examined the biomass of insects in relation to temperature and time of season. Our samples mostly contained Diptera (33%), Lepidoptera (19%), Hymenoptera (18%), and Coleoptera (10%). We found strong regional differences in the phenology of insects and their response to temperature, even within the same taxonomic group, habitat type, and time of season. For example, the biomass of nematoceran flies increased across the season in the central part of the continent, but it only showed a small increase in the Northeast and a seasonal decline in the Southeast and West. At a smaller scale, insect biomass at different traps operating on the same days was correlated up to ~75 km apart. Large‐scale geographic and phenological variation in insect biomass and abundance has not been studied well, and it is a major source of controversy in previous analyses of insect declines that have aggregated studies from different locations and time periods. Our study illustrates that large‐scale predictions about changes in insect populations, and their causes, will need to incorporate regional and taxonomic differences in the response to temperature.

On-road remote sensing of vehicles in Dublin: Measurement and emission factor estimation - Srinath Mahesh; Aonghus McNabola; William Smith; David Timoney; Ali Ekhtiari; Ben Fowler; Paul Willis; Rebecca Rose; Jasmine Wareham; Hannah Walker; Bidisha Ghosh (Transportation Research Part D: Transport and Environment, 2023)

Habitat value of subsea wells and pipelines for fishery target species in Australia - Dianne McLean; Conrad W. Speed; Matthew Jon Birt; Jamie Colquhoun; Mark Case; Marcus Stowar; Todd Bond; Daniel Ierodiaconou; Sasha K. Whitmarsh; Michael D. Taylor; Sam Wines; David John Booth; et al. (Frontiers in Marine Science, 2022)
Subsea pipelines and wells installed to support the oil and gas industry represent some of the most extensive and numerous anthropogenic structures throughout global marine ecosystems. There remains a paucity of information on the habitat value of these structures for fishery target species and, as a result, little understanding of how decommissioning should be conducted to minimise impacts to populations of these economically and socially important species. We assess the diversity and abundance of species that are targets of recreational and commercial fisheries on 33 subsea wells and 17 pipelines across the tropical northwest and temperate southeast marine regions of Australia. We examine relationships between fish identity and abundance and a range of environmental (e.g., depth, location), infrastructure-specific (e.g., pipeline position, diameter, age, length of pipeline, height of well, position on well), and biological (% cover of epibiota) variables using video filmed by remotely operated vehicles during their routine offshore inspection and maintenance campaigns. A total of 100 fishery target species were observed across subsea well and pipeline infrastructure, 56 species uniquely observed on pipelines and nine unique to wells. The families Lutjanidae (snapper), Serranidae (rock cods, groupers, perch), and Carangidae (trevallies) were most common and abundant on both wells and pipelines. In the northwest, lutjanids were most abundant around the base of wells, in shallow depths, on shorter wells, and where pipelines spanned the seafloor. A greater number of fishery target species and abundance of ocean perch ( Helicolenus spp.) were also associated with pipelines that spanned the seafloor in temperate southeast Australia. The combined biomass of three species of snapper on wells in the northwest was 1,270 kg, with production levels for these species on each well estimated to be 105.2 g m 2 year -1 . The present study serves as an important reference point for informing decommissioning decisions for pipeline and well infrastructure and demonstrates the utility of industry-held data for science. We suggest that key predictor variables identified here be incorporated into comprehensive before-after-control-impact scientific studies for specific fields/assets to enable the prediction of potential impacts of decommissioning scenarios on marine communities present and quantification of such impacts after the decommissioning activity has occurred.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Recruiting a long way from home: Domino damselfish Dascyllus trimaculatus can detect new temperate coral habitat and conspecifics - Max J. O'Connell; Ashley M. Fowler; Sam J. Allan; Giglia A. Beretta; David J. Booth (Journal of Fish Biology, 2022)
Climate change is driving tropicalisation of temperate reefs, yet it is unclear how range‐shifting tropical fishes locate suitable habitat. The authors tested whether juvenile tropical damsels Dascyllus trimaculatus could detect rare coral habitat ( Pocillopora aliciae ) and conspecifics on temperate rocky reefs using olfactory and visual preference experiments. For all cues, individuals selected and spent more time than expected in aquarium areas with the cue present, which included coral odour and conspecific odour and visual cues. This indicates that vagrant coral‐reef fish can detect rare suitable habitat outside of their natal range.

Influence of offshore oil and gas structures on seascape ecological connectivity - Dianne L. McLean; Luciana C. Ferreira; Jessica A. Benthuysen; Karen J. Miller; Marie‐Lise Schläppy; Matthew J. Ajemian; Oliver Berry; Silvana N. R. Birchenough; Todd Bond; Fabio Boschetti; Ann S. Bull; Jeremy T. Claisse; et al. (Global Change Biology, 2022)
Offshore platforms, subsea pipelines, wells and related fixed structures supporting the oil and gas (O&G) industry are prevalent in oceans across the globe, with many approaching the end of their operational life and requiring decommissioning. Although structures can possess high ecological diversity and productivity, information on how they interact with broader ecological processes remains unclear. Here, we review the current state of knowledge on the role of O&G infrastructure in maintaining, altering or enhancing ecological connectivity with natural marine habitats. There is a paucity of studies on the subject with only 33 papers specifically targeting connectivity and O&G structures, although other studies provide important related information. Evidence for O&G structures facilitating vertical and horizontal seascape connectivity exists for larvae and mobile adult invertebrates, fish and megafauna; including threatened and commercially important species. The degree to which these structures represent a beneficial or detrimental net impact remains unclear, is complex and ultimately needs more research to determine the extent to which natural connectivity networks are conserved, enhanced or disrupted. We discuss the potential impacts of different decommissioning approaches on seascape connectivity and identify, through expert elicitation, critical knowledge gaps that, if addressed, may further inform decision making for the life cycle of O&G infrastructure, with relevance for other industries (e.g. renewables). The most highly ranked critical knowledge gap was a need to understand how O&G structures modify and influence the movement patterns of mobile species and dispersal stages of sessile marine species. Understanding how different decommissioning options affect species survival and movement was also highly ranked, as was understanding the extent to which O&G structures contribute to extending species distributions by providing rest stops, foraging habitat, and stepping stones. These questions could be addressed with further dedicated studies of animal movement in relation to structures using telemetry, molecular techniques and movement models. Our review and these priority questions provide a roadmap for advancing research needed to support evidence‐based decision making for decommissioning O&G infrastructure.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Use of plastid genome sequences in phylogeographic studies of tree species can be misleading without comprehensive sampling of co-occurring, related species - Patrick S. Fahey; Rachael M. Fowler; Frank Udovicic; David J. Cantrill; Michael J. Bayly (Tree Genetics & Genomes, 2021)

A biallelic variant in CLRN2 causes non-syndromic hearing loss in humans - Barbara Vona; Neda Mazaheri; Sheng-Jia Lin; Lucy A. Dunbar; Reza Maroofian; Hela Azaiez; Kevin T. Booth; Sandrine Vitry; Aboulfazl Rad; Franz Rüschendorf; Pratishtha Varshney; Ben Fowler; et al. (Human Genetics, 2021)
Deafness, the most frequent sensory deficit in humans, is extremely heterogeneous with hundreds of genes involved. Clinical and genetic analyses of an extended consanguineous family with pre-lingual, moderate-to-profound autosomal recessive sensorineural hearing loss, allowed us to identify CLRN2, encoding a tetraspan protein, as a new deafness gene. Homozygosity mapping followed by exome sequencing identified a 14.96 Mb locus on chromosome 4p15.32p15.1 containing a likely pathogenic missense variant in CLRN2 (c.494C > A, NM_001079827.2) segregating with the disease. Using in vitro RNA splicing analysis, we show that the CLRN2 c.494C > A variant leads to two events: (1) the substitution of a highly conserved threonine (uncharged amino acid) to lysine (charged amino acid) at position 165, p.(Thr165Lys), and (2) aberrant splicing, with the retention of intron 2 resulting in a stop codon after 26 additional amino acids, p.(Gly146Lysfs*26). Expression studies and phenotyping of newly produced zebrafish and mouse models deficient for clarin 2 further confirm that clarin 2, expressed in the inner ear hair cells, is essential for normal organization and maintenance of the auditory hair bundles, and for hearing function. Together, our findings identify CLRN2 as a new deafness gene, which will impact future diagnosis and treatment for deaf patients.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Growth impacts in a changing ocean: insights from two coral reef fishes in an extreme environment - Daniele D’Agostino; John A. Burt; Veronica Santinelli; Grace O. Vaughan; Ashley M. Fowler; Tom Reader; Brett M. Taylor; Andrew S. Hoey; Geórgenes H. Cavalcante; Andrew G. Bauman; David A. Feary (Coral Reefs, 2021)
Determining the life-history consequences for fishes living in extreme and variable environments will be vital in predicting the likely impacts of ongoing climate change on reef fish demography. Here, we compare size-at-age and maximum body size of two common reef fish species ( Lutjanus ehrenbergii and Pomacanthus maculosus ) between the environmentally extreme Arabian/Persian Gulf (‘Arabian Gulf’) and adjacent comparably benign Oman Sea. Additionally, we use otolith increment width profiles to investigate the influence of temperature, salinity and productivity on the individual growth rates. Individuals of both species showed smaller size-at-age and lower maximum size in the Arabian Gulf compared to conspecifics in the less extreme and less variable environment of the Oman Sea, suggesting a life-history trade-off between size and metabolic demands. Salinity was the best environmental predictor of interannual growth across species and regions, with low growth corresponding to more saline conditions. However, salinity had a weaker negative effect on interannual growth of fishes in the Arabian Gulf than in the Oman Sea, indicating Arabian Gulf populations may be better able to acclimate to changing environmental conditions. Temperature had a weak positive effect on the interannual growth of fishes in the Arabian Gulf, suggesting that these populations may still be living within their thermal windows. Our results highlight the potential importance of osmoregulatory cost in impacting growth, and the need to consider the effect of multiple stressors when investigating the consequences of future climate change on fish demography.

Enhancing the Scientific Value of Industry Remotely Operated Vehicles (ROVs) in Our Oceans - Dianne L. McLean; Miles J. G. Parsons; Andrew R. Gates; Mark C. Benfield; Todd Bond; David J. Booth; Michael Bunce; Ashley M. Fowler; Euan S. Harvey; Peter I. Macreadie; Charitha B. Pattiaratchi; Sally Rouse; et al. (Frontiers in Marine Science, 2020)

Calretinin is a novel candidate marker for adverse ovarian effects of early life exposure to mixtures of endocrine disruptors in the rat - Hanna Katarina Lilith Johansson; Terje Svingen; Julie Boberg; Paul A. Fowler; David Stead; Anne Marie Vinggaard; Panagiotis Filis (Archives of Toxicology, 2020)
Disruption of sensitive stages of ovary development during fetal and perinatal life can have severe and life-long consequences for a woman’s reproductive life. Exposure to endocrine disrupting chemicals may affect ovarian development, leading to subsequent reproductive disorders. Here, we investigated the effect of early life exposure to defined mixtures of human-relevant endocrine disrupting chemicals on the rat ovary. We aimed to identify molecular events involved in pathogenesis of ovarian dysgenesis syndrome that have potential for future adverse outcome pathway development. We therefore focused on the ovarian proteome. Rats were exposed to a mixture of phthalates, pesticides, UV-filters, bisphenol A, butyl-paraben, and paracetamol during gestation and lactation. The chemicals were tested together or in subgroups of chemicals with anti-androgenic or estrogenic potentials at doses 450-times human exposure. Paracetamol was tested separately, at a dose of 360 mg/kg. Using shotgun proteomics on ovaries from pup day 17 offspring, we observed exposure effects on the proteomes. Nine proteins were affected in more than one exposure group and of these, we conclude that calretinin is a potential key event biomarker of early endocrine disruption in the ovary.

Thermodynamic controls of the Western Tibetan Vortex on Tibetan air temperature - Xiao-Feng Li; Hayley J. Fowler; Jingjing Yu; Nathan Forsythe; Stephen Blenkinsop; David Pritchard (Climate Dynamics, 2019)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Global Observing Needs in the Deep Ocean - Lisa A. Levin; Brian J. Bett; Andrew R. Gates; Patrick Heimbach; Bruce M. Howe; Felix Janssen; Andrea McCurdy; Henry A. Ruhl; Paul Snelgrove; Karen I. Stocks; David Bailey; Simone Baumann-Pickering; et al. (Frontiers in Marine Science, 2019)

The status of the invertebrate fauna on the South Atlantic island of St Helena: problems, analysis, and recommendations - Alan Gray; Vicky Wilkins; David Pryce; Liza Fowler; Roger S. Key; Howard Mendel; Michael Jervois; Axel Hochkirch; Rebecca Cairns-Wicks; Amy-Jayne Dutton; Lourens Malan (Biodiversity and Conservation, 2019)

The colour of environmental fluctuations associated with terrestrial animal population dynamics - David Gilljam; Jonas Knape; Andreas Lindén; Marianne Mugabo; Steven M. Sait; Mike S. Fowler (Global Ecology and Biogeography, 2019)
Aim The temporal structure (colour) of environmental variation influences population fluctuations, extinction risk and community stability. However, it is unclear whether environmental covariates linked to population fluctuations are distinguishable from a purely random process (white noise). We aimed to estimate colour coefficients and relative support for three models commonly representing coloured stochastic processes, in environmental series linked to terrestrial animal population fluctuations. Location North America and Eurasia. Time period 1901–2002. Major taxa studied Birds, insects and mammals. Methods We analysed multiple abiotic environmental covariates, comparing point estimates and confidence intervals of temporal structure in competing models fitted using white noise, autoregressive [AR(1)] and 1/ f processes in the time domain and the frequency domain (where time series were analysed after decomposition into different sinusoidal frequencies and their relative powers). All animal time series were sampled annually for ≤ 50 years, potentially inflating type II errors. We also considered 101‐year series of matched environmental covariates, performing a statistical power analysis evaluating our ability to draw robust conclusions. Results Temperature‐related variables were associated with the largest fraction of population fluctuations. Ninety‐three per cent of shorter environmental series were indistinguishable from white noise, limited by time‐series length and associated with wide confidence intervals. The longer environmental series analysed in the time domain offered sufficiently high statistical power to identify correctly colour estimates ≥ |0.27|, indicating that 20% of series were best described by a slightly reddened noise process. Main conclusions Focusing on the short time‐scales typically available for ecologists, most environmental variables associated with terrestrial animal population fluctuations are best characterized by white noise processes, although type II errors are common. The correct detection of intermediately coloured noise with power 0.8 requires ≥ 16 data points in the time domain or ≥ 47 points in the frequency domain. Over longer time‐scales, where type II errors are less likely, one‐fifth of populations are associated with coloured (often reddened) variables.

Some Old Movies Become Classics – A Case Study Determining the Scientific Value of ROV Inspection Footage on a Platform on Australia’s North West Shelf - Paul G. Thomson; Ashley M. Fowler; Andrew R. Davis; Charitha B. Pattiaratchi; David J. Booth (Frontiers in Marine Science, 2018)

Storylines: an alternative approach to representing uncertainty in physical aspects of climate change - Theodore G. Shepherd; Emily Boyd; Raphael A. Calel; Sandra C. Chapman; Suraje Dessai; Ioana M. Dima-West; Hayley J. Fowler; Rachel James; Douglas Maraun; Olivia Martius; Catherine A. Senior; Adam H. Sobel; et al. (Climatic Change, 2018)

New poleward observations of 30 tropical reef fishes in temperate southeastern Australia - Ashley M. Fowler; Kerryn Parkinson; David J. Booth (Marine Biodiversity, 2018)

The Karakoram/Western Tibetan vortex: seasonal and year-to-year variability - Xiao-Feng Li; Hayley J. Fowler; Nathan Forsythe; Stephen Blenkinsop; David Pritchard (Climate Dynamics, 2018)

Erratum to: Modelling foetal exposure to maternal smoking using hepatoblasts from pluripotent stem cells - Baltasar Lucendo-Villarin; Panagiotis Filis; Madeleine J. Swortwood; Marilyn A. Huestis; Jose Meseguer-Ripolles; Kate Cameron; John P. Iredale; Peter J. O’Shaughnessy; Paul A. Fowler; David C. Hay (Archives of Toxicology, 2017)

Modelling foetal exposure to maternal smoking using hepatoblasts from pluripotent stem cells - Baltasar Lucendo-Villarin; Panagiotis Filis; Madeleine J. Swortwood; Marilyn A. Huestis; Jose Meseguer-Ripolles; Kate Cameron; John P. Iredale; Peter J. O’Shaughnessy; Paul A. Fowler; David C. Hay (Archives of Toxicology, 2017)

Boom‐bust dynamics in biological invasions: towards an improved application of the concept - David L. Strayer; Carla M. D'Antonio; Franz Essl; Mike S. Fowler; Juergen Geist; Sabine Hilt; Ivan Jarić; Klaus Jöhnk; Clive G. Jones; Xavier Lambin; Alexander W. Latzka; Jan Pergl; et al. (Ecology Letters, 2017)
Boom‐bust dynamics – the rise of a population to outbreak levels, followed by a dramatic decline – have been associated with biological invasions and offered as a reason not to manage troublesome invaders. However, boom‐bust dynamics rarely have been critically defined, analyzed, or interpreted. Here, we define boom‐bust dynamics and provide specific suggestions for improving the application of the boom‐bust concept. Boom‐bust dynamics can arise from many causes, some closely associated with invasions, but others occurring across a wide range of ecological settings, especially when environmental conditions are changing rapidly. As a result, it is difficult to infer cause or predict future trajectories merely by observing the dynamic. We use tests with simulated data to show that a common metric for detecting and describing boom‐bust dynamics, decline from an observed peak to a subsequent trough, tends to severely overestimate the frequency and severity of busts, and should be used cautiously if at all. We review and test other metrics that are better suited to describe boom‐bust dynamics. Understanding the frequency and importance of boom‐bust dynamics requires empirical studies of large, representative, long‐term data sets that use clear definitions of boom‐bust, appropriate analytical methods, and careful interpretations.

The Significant Surface-Water Connectivity of “Geographically Isolated Wetlands” - Aram J. K. Calhoun; David M. Mushet; Laurie C. Alexander; Edward S. DeKeyser; Laurie Fowler; Charles R. Lane; Megan W. Lang; Mark C. Rains; Stephen C. Richter; Susan C. Walls (Wetlands, 2017)

The city as a refuge for insect pollinators - Damon M. Hall; Gerardo R. Camilo; Rebecca K. Tonietto; Jeff Ollerton; Karin Ahrné; Mike Arduser; John S. Ascher; Katherine C. R. Baldock; Robert Fowler; Gordon Frankie; Dave Goulson; Bengt Gunnarsson; et al. (Conservation Biology, 2017)
Research on urban insect pollinators is changing views on the biological value and ecological importance of cities. The abundance and diversity of native bee species in urban landscapes that are absent in nearby rural lands evidence the biological value and ecological importance of cities and have implications for biodiversity conservation. Lagging behind this revised image of the city are urban conservation programs that historically have invested in education and outreach rather than programs designed to achieve high‐priority species conservation results. We synthesized research on urban bee species diversity and abundance to determine how urban conservation could be repositioned to better align with new views on the ecological importance of urban landscapes. Due to insect pollinators’ relatively small functional requirements—habitat range, life cycle, and nesting behavior—relative to larger mammals, we argue that pollinators put high‐priority and high‐impact urban conservation within reach. In a rapidly urbanizing world, transforming how environmental managers view the city can improve citizen engagement and contribute to the development of more sustainable urbanization.

Performance on the Cogstate Brief Battery Is Related to Amyloid Levels and Hippocampal Volume in Very Mild Dementia - Yen Ying Lim; Victor L. Villemagne; Simon M. Laws; Robert H. Pietrzak; David Ames; Christopher Fowler; Stephanie Rainey-Smith; Peter J. Snyder; Pierrick Bourgeat; Ralph N. Martins; Olivier Salvado; Christopher C. Rowe; et al. (Journal of Molecular Neuroscience, 2016)

Temperate predators and seasonal water temperatures impact feeding of a range expanding tropical fish - Hayden J. Beck; David A. Feary; Ashley M. Fowler; Elizabeth M. P. Madin; David J. Booth (Marine Biology, 2016)

Developmental regulation of metabolites and low temperature tolerance in lines of crosses between spring and winter wheat - Mohsen Hosseini; Reza Maali-Amiri; Siroos Mahfoozi; David Brian Fowler; Rahmat Mohammadi (Acta Physiologiae Plantarum, 2016)

Geographically Isolated Wetlands: Rethinking a Misnomer - David M. Mushet; Aram J. K. Calhoun; Laurie C. Alexander; Matthew J. Cohen; Edward S. DeKeyser; Laurie Fowler; Charles R. Lane; Megan W. Lang; Mark C. Rains; Susan C. Walls (Wetlands, 2015)

Evaluating Abiotic Influences on Soil Salinity of Inland Managed Wetlands and Agricultural Croplands in a Semi-Arid Environment - Drew N. Fowler; Sammy L. King; David C. Weindorf (Wetlands, 2014)

Latitudinal shifts in coral reef fishes: why some species do and others do not shift - David A Feary; Morgan S Pratchett; Micheal J Emslie; Ashley M Fowler; Will F Figueira; Osmar J Luiz; Yohei Nakamura; David J Booth (Fish and Fisheries, 2014)
Climate change is resulting in rapid poleward shifts in the geographical distribution of many tropical fish species, but it is equally apparent that some fishes are failing to exhibit expected shifts in their geographical distribution. There is still little understanding of the species‐specific traits that may constrain or promote successful establishment of populations in temperate regions. We review the factors likely to affect population establishment, including larval supply, settlement and post‐settlement processes. In addition, we conduct meta‐analyses on existing and new data to examine relationships between species‐specific traits and vagrancy. We show that tropical vagrant species are more likely to originate from high‐latitude populations, while at the demographic level, tropical fish species with large body size, high swimming ability, large size at settlement and pelagic spawning behaviour are more likely to show successful settlement into temperate habitats. We also show that both habitat and food limitation at settlement and within juvenile stages may constrain tropical vagrant communities to those species with medium to low reliance on coral resources.

Inertia in an ombrotrophic bog ecosystem in response to 9 years' realistic perturbation by wet deposition of nitrogen, separated by form - Lucy J. Sheppard; Ian D. Leith; Toshie Mizunuma; Sarah Leeson; Sanna Kivimaki; J. Neil Cape; Netty van Dijk; David Leaver; Mark A. Sutton; David Fowler; Leon J.L. Van den Berg; Alan Crossley; et al. (Global Change Biology, 2014)
Wet deposition of nitrogen (N) occurs in oxidized (nitrate) and reduced (ammonium) forms. Whether one form drives vegetation change more than the other is widely debated, as field evidence has been lacking. We are manipulating N form in wet deposition to an ombrotrophic bog, Whim (Scottish Borders), and here report nine years of results. Ammonium and nitrate were provided in rainwater spray as NH 4 Cl or NaNO 3 at 8, 24 or 56 kg N ha −1 yr −1 , plus a rainwater only control, via an automated system coupled to site meteorology. Detrimental N effects were observed in sensitive nonvascular plant species, with higher cumulative N loads leading to more damage at lower annual doses. Cover responses to N addition, both in relation to form and dose, were species specific and mostly dependent on N dose. Some species were generally indifferent to N form and dose, while others were dose sensitive. Calluna vulgaris showed a preference for higher N doses as ammonium N and Hypnum jutlandicum for nitrate N. However, after 9 years, the magnitude of change from wet deposited N on overall species cover is small, indicating only a slow decline in key species. Nitrogen treatment effects on soil N availability were likewise small and rarely correlated with species cover. Ammonium caused most N accumulation and damage to sensitive species at lower N loads, but toxic effects also occurred with nitrate. However, because different species respond differently to N form, setting of ecosystem level critical loads by N form is challenging. We recommend implementing the lowest value of the critical load range where communities include sensitive nonvascular plants and where ammonium dominates wet deposition chemistry. In the context of parallel assessment at the same site, N treatments for wet deposition showed overall much smaller effects than corresponding inputs of dry deposition as ammonia.

Priority research questions for the UK food system - John S. I. Ingram; Hugh L. Wright; Lucy Foster; Timothy Aldred; David Barling; Tim G. Benton; Paul M. Berryman; Charles S. Bestwick; Alice Bows-Larkin; Tim F. Brocklehurst; Judith Buttriss; John Casey; et al. (Food Security, 2013)
The rise of food security up international political, societal and academic agendas has led to increasing interest in novel means of improving primary food production and reducing waste. There are however, also many ‘post-farm gate’ activities that are critical to food security, including processing, packaging, distributing, retailing, cooking and consuming. These activities all affect a range of important food security elements, notably availability, affordability and other aspects of access, nutrition and safety. Addressing the challenge of universal food security, in the context of a number of other policy goals (e.g. social, economic and environmental sustainability), is of keen interest to a range of UK stakeholders but requires an up-to-date evidence base and continuous innovation. An exercise was therefore conducted, under the auspices of the UK Global Food Security Programme, to identify priority research questions with a focus on the UK food system (though the outcomes may be broadly applicable to other developed nations). Emphasis was placed on incorporating a wide range of perspectives (‘world views’) from different stakeholder groups: policy, private sector, non-governmental organisations, advocacy groups and academia. A total of 456 individuals submitted 820 questions from which 100 were selected by a process of online voting and a three-stage workshop voting exercise. These 100 final questions were sorted into 10 themes and the ‘top’ question for each theme identified by a further voting exercise. This step also allowed four different stakeholder groups to select the top 7–8 questions from their perspectives. Results of these voting exercises are presented. It is clear from the wide range of questions prioritised in this exercise that the different stakeholder groups identified specific research needs on a range of post-farm gate activities and food security outcomes. Evidence needs related to food affordability, nutrition and food safety (all key elements of food security) featured highly in the exercise. While there were some questions relating to climate impacts on production, other important topics for food security (e.g. trade, transport, preference and cultural needs) were not viewed as strongly by the participants.

Does increasing the spatial resolution of a regional climate model improve the simulated daily precipitation? - Steven C. Chan; Elizabeth J. Kendon; Hayley J. Fowler; Stephen Blenkinsop; Christopher A. T. Ferro; David B. Stephenson (Climate Dynamics, 2013)

Mobile receivers: releasing the mooring to ‘see’ where fish go - Sean A. Hayes; Nicole M. Teutschel; Cyril J. Michel; Cory Champagne; Patrick W. Robinson; Melinda Fowler; Tina Yack; David K. Mellinger; Samantha Simmons; Daniel P. Costa; R. Bruce MacFarlane (Environmental Biology of Fishes, 2013)

Methane emissions from soils: synthesis and analysis of a large UK data set - Peter E. Levy; Annette Burden; Mark D. A. Cooper; Kerry J. Dinsmore; Julia Drewer; Chris Evans; David Fowler; Jenny Gaiawyn; Alan Gray; Stephanie K. Jones; Timothy Jones; Niall P. McNamara; et al. (Global Change Biology, 2012)
Nearly 5000 chamber measurements of CH 4 flux were collated from 21 sites across the U nited K ingdom, covering a range of soil and vegetation types, to derive a parsimonious model that explains as much of the variability as possible, with the least input requirements. Mean fluxes ranged from −0.3 to 27.4 nmol CH 4 m −2 s −1 , with small emissions or low rates of net uptake in mineral soils (site means of −0.3 to 0.7 nmol m −2 s −1 ) and much larger emissions from organic soils (site means of −0.3 to 27.4 nmol m −2 s −1 ). Less than half of the observed variability in instantaneous fluxes could be explained by independent variables measured. The reasons for this include measurement error, stochastic processes and, probably most importantly, poor correspondence between the independent variables measured and the actual variables influencing the processes underlying methane production, transport and oxidation. When temporal variation was accounted for, and the fluxes averaged at larger spatial scales, simple models explained up to ca. 75% of the variance in CH 4 fluxes. Soil carbon, peat depth, soil moisture and pH together provided the best sub‐set of explanatory variables. However, where plant species composition data were available, this provided the highest explanatory power. Linear and nonlinear models generally fitted the data equally well, with the exception that soil moisture required a power transformation. To estimate the impact of changes in peatland water table on CH 4 emissions in the U nited K ingdom, an emission factor of +0.4 g CH 4 m −2 yr −1 per cm increase in water table height was derived from the data.

Opportunities from Remote Sensing for Supporting Water Resources Management in Village/Valley Scale Catchments in the Upper Indus Basin - Nathan Forsythe; Hayley J. Fowler; Chris G. Kilsby; David R. Archer (Water Resources Management, 2012)

Influence of insects and fungal pathogens on individual and population parameters of Cirsium arvense in its native and introduced ranges - Michael G. Cripps; Graeme W. Bourdôt; David J. Saville; Hariet L. Hinz; Simon V. Fowler; Grant R. Edwards (Biological Invasions, 2011)

Dry deposition of ammonia gas drives species change faster than wet deposition of ammonium ions: evidence from a long‐term field manipulation - Lucy J. Sheppard; Ian D. Leith; Toshie Mizunuma; John Neil Cape; Alan Crossley; Sarah Leeson; Mark A. Sutton; Netty van Dijk; David Fowler (Global Change Biology, 2011)
Although the effects of atmospheric nitrogen deposition on species composition are relatively well known, the roles of the different forms of nitrogen, in particular gaseous ammonia ( NH 3 ), have not been tested in the field. Since 2002, we have manipulated the form of N deposition to an ombrotrophic bog, W him, on deep peat in southern S cotland, with low ambient N (wet + dry = 8 kg N ha −1 yr −1 ) and S (4 kg S ha −1 yr −1 ) deposition. A gradient of ammonia ( NH 3 , dry N ), from 70 kg N ha −1 yr −1 down to background, 3–4 kg N ha −1 yr −1 was generated by free air release. Wet ammonium ( NH 4 + , wet N) was provided to replicate plots in a fine rainwater spray ( NH 4 Cl at +8, +24, +56 kg N ha −1 yr −1 ). Automated treatments are coupled to meteorological conditions, in a globally unique, field experiment. Ammonia concentrations were converted to NH 3 ‐ N deposition (kg N ha −1 ) using a site/vegetation specific parameterization. Within 3 years, exposure to relatively modest deposition of NH 3 , 20–56 kg NH 3 ‐N ha −1 yr −1 led to dramatic reductions in species cover, with almost total loss of C alluna vulgaris , S phagnum capillifolium and C ladonia portentosa . These effects appear to result from direct foliar uptake and interaction with abiotic and biotic stresses, rather than via effects on the soil. Additional wet N by contrast, significantly increased C alluna cover after 5 years at the 56 kg N dose, but reduced cover of S phagnum and C ladonia . Cover reductions caused by wet N were significantly different from and much smaller than those caused by equivalent dry N doses. The effects of gaseous NH 3 described here, highlight the potential for ammonia to destroy acid heathland and peat bog ecosystems. Separating the effects of gaseous ammonia and wet ammonium deposition, for a peat bog, has significant implications for regulatory bodies and conservation agencies.

Enemy release does not increase performance of Cirsium arvense in New Zealand - Michael G. Cripps; Grant R. Edwards; Graeme W. Bourdôt; David J. Saville; Hariet L. Hinz; Simon V. Fowler (Plant Ecology, 2010)

Are prediction models for Lynch syndrome valid for probands with endometrial cancer? - Floor J. Backes; Heather Hampel; Katherine A. Backes; Luis Vaccarello; George Lewandowski; Jeffrey A. Bell; Gary C. Reid; Larry J. Copeland; Jeffrey M. Fowler; David E. Cohn (Familial Cancer, 2009)

SEASONAL OCCURRENCE OF NORTH ATLANTIC RIGHT WHALE ( EUBALAENA GLACIALIS ) VOCALIZATIONS AT TWO SITES ON THE SCOTIAN SHELF - David K. Mellinger; Sharon L. Nieukirk; Haru Matsumoto; Sara L. Heimlich; Robert P. Dziak; Joe Haxel; Matt Fowler; Christian Meinig; Hendrick V. Miller (Marine Mammal Science, 2007)
A year‐long acoustic survey for critically endangered North Atlantic right whales was conducted at two sites on the central and western Scotian Shelf. Autonomous hydrophones recorded sound continuously from July 2004 to August 2005. Right whale contact calls (upcalls) were identified using automatic recognition software, and the resulting detections were checked manually. Substantial numbers of hours with upcalls were observed at both sites, with approximately four times as many hours with calls at the western site as the central one. Calls occurred mainly from August through October, with the earliest calls in late June and the latest at the end of December at both sites. In addition to this seasonal trend, there was a significant diel pattern in calling at the central site but not at the more westerly site. Results are analyzed in light of feeding ecology and broad‐scale movements of right whales.

Estimated Sand and Gravel Resources of the South Merrimack, Hillsborough County, New Hampshire, 7.5-Minute Quadrangle - David M. Sutphin; Lawrence J. Drew; Brian K. Fowler (Natural Resources Research, 2007)

Human BAC-mediated rescue of the Friedreich ataxia knockout mutation in transgenic mice - Joseph P. Sarsero; Lingli Li; Timothy P. Holloway; Lucille Voullaire; Sophie Gazeas; Kerry J. Fowler; Denise M. Kirby; David R. Thorburn; Adam Galle; Surindar Cheema; Michel Koenig; Robert Williamson; et al. (Mammalian Genome, 2004)

Comparison of the Effects of Wet N Deposition (NH4Cl) and Dry N Deposition (NH3) on UK Moorland Species - Ian D. Leith; Lucy J. Sheppard; Carole E.R. Pitcairn; J. Neil Cape; Paul W. Hill; Valerie H. Kennedy; Y. Sim Tang; Ron I. Smith; David Fowler (Water, Air, & Soil Pollution, 2001)

Foliar Nitrogen as an Indicator of Nitrogen Deposition and Critical Loads Exceedance on a European Scale - Carole E.R. Pitcairn; Ian D. Leith; David Fowler; Ken J. Hargreaves; Masoud Moghaddam; Valerie H. Kennedy; Lennart Granat (Water, Air, & Soil Pollution, 2001)

Measurements of Ozone Deposition to Vegetation Quantifying the Flux, the Stomatal and Non-Stomatal Components - David Fowler; Chris Flechard; J. Neil Cape; Robert L. Storeton-West; Mhairi Coyle (Water, Air, & Soil Pollution, 2001)

Advances in micrometeorological methods for the measurement and interpretation of gas and particle nitrogen fluxes - David Fowler; Mhairi Coyle; Chris Flechard; Ken Hargreaves; Eiko Nemitz; Robert Storeton-West; Mark Sutton; Jan-Willem Erisman (Plant and Soil, 2001)

Biosphere-atmosphere interactions of ammonia with grasslands: Experimental strategy and results from a new European initiative - M.A. Sutton; C. Milford; E. Nemitz; M.R. Theobald; P.W. Hill; D. Fowler; J.K. Schjoerring; M.E. Mattsson; K.H. Nielsen; S. Husted; J.W. Erisman; R. Otjes; et al. (Plant and Soil, 2001)

Acknowledgements - Lucy Sheppard; Neil Cape; David Fowler (Water, Air, & Soil Pollution, 1999)

Preface - Lucy Sheppard; David Fowler (Water, Air, & Soil Pollution, 1999)

The Global Exposure of Forests to Air Pollutants - David Fowler; J. Neil Cape; Mhairi Coyle; Chris Flechard; Johan Kuylenstierna; Kevin Hicks; Dick Derwent; Colin Johnson; David Stevenson (Water, Air, & Soil Pollution, 1999)

Methane emission by termites and oxidation by soils, across a forest disturbance gradient in the Mbalmayo Forest Reserve, Cameroon - Jannette A. Macdonald; PauL. Eggleton; David E. Bignell; Francis Forzi; David Fowler (Global Change Biology, 1998)
Methane fluxes were measured, using static chambers, across a disturbance gradient in a West African semi‐deciduous humid forest. Soil‐feeding termite biomass was simultaneously determined, in an attempt to examine its influence on the net soil‐atmosphere exchange of CH 4 . CH 4 emission rates from individual termite species were determined under laboratory conditions, permitting the gross production of CH 4 to be compared with net fluxes to the atmosphere. Both net CH 4 oxidation(‐) and emission were observed, and CH 4 fluxes ranged from – 24.6 to 40.7 ng m –2 s –1 . A statistically significant relationship between termite biomass and CH 4 flux was observed across the forested sites such that: CH 4 flux (ng m –2 s –1 ) = 4.95 × termite biomass (gm –2 )–10.9 ( P 4 oxidation were on average 60% smaller at the clearfelled and Terminalia plantation sites than at the near‐primary forest site. Two of the disturbed sites were net CH 4 sources during one of the sampling periods. Disturbance of tropical forests, resulting in a decrease in the CH 4 sink capacity of the soil, may therefore increase the contribution of termite‐derived CH 4 to the atmosphere. Measurements from the mounds of the soil‐feeding termites Thoracotermes macrothorax and Cubitermes fungifaber from the old plantation site gave a CH 4 emission of 636 and 53.4 ng s –1 mound –1 , respectively. The forest floor surrounding the mounds was sampled in three concentric bands. Around the mound of T. macrothorax the soil was a net source of CH 4 estimated to contribute a further 148 ng s –1 . Soil surrounding the mound of C. fungifaber was mostly a net sink. The mounds of soil‐feeding termites are point sources of CH 4 , which at the landscape scale may exceed the general sink capacity of the soil, to an extent dependent on seasonal variations in soil moisture and level of disturbance.